PEMIKIRAN ETIKA MULLA SHADRA - Bachtiar, Andi Safri (P3M STAIN Parepare, 2017)
The muslim thinkers argue that ethic is the science of spirit therapy that is necessary  for human being and even is in a uncertain condition like psychology  and mental societies lately who show unstable moral decadence. Hence, the study of ethic aspect is so urgent. Besides, philosophical ethic that is developed by the muslim philosophers need to get the attention seriously. One of them having the essential role for intellectual world of Islam is Mulla Shadra. In his Era, Mulla Shadra built a nuance for new philosophy that is learned intensively with kind of the analysis as well as imparting syntheses and integrations from previous philosophers. By the thought in briliant and original philosophy aspect, he is able to answer all moral challenges in his era.